The Mitogen-Activated Protein Kinase (MAPKs) Expression and Primary Stress Hormone (Cortisol) of Clarias sp. Juvenile in Different Light Intensity - Agoes Soeprijanto; R Adharyan Islamy (Journal of Aquaculture and Fish Health, 2023)
Clarias sp. is one of major genera of freshwater catfish and also common commodity in tropical aquaculture. Excessive light intensity is expected to be responded to by fish as environmental stressors. Fish that experience stress will increase the secretion of catecholamine, cortisol, blood glucose levels and p38 MAPKs in catfish. The different intensity of lights will affect the fish physiological processes. The purpose of this study was to analyze physiological responses (Level of blood glucose, primary stress hormone (Cortisol) and p38 MAPKs) catfish Clarias sp. which were incubated at different lights intensity of catfish. 300 fish were collected from Kepanjen Regency, East Java. Blood and meat sampling are carried out to test the profile of glucose, cortisol, and p38 MAPKs. The experimental research at this stage were carried out by transferred the catfish from Kepanjen to experimental aquarium (50 x 30 x 30 cm) that setted the different lights intensity (0 lux (control), 400 lux, 800 lux and 1200 lux). Each experimental aquarium is filled with 15 catfish and will be kept it for 21 days. Quantificationof the parameter using ELISA method. The study result showed highest peak of primary stress hormone (cortisol) levels are 34±1,50 ng/mL, blood glucose levels are 120±3,4 mg/dL, and p38 MAPK are 97±1,1 %. All of it were achieved in the treatment of 1200 lux on the 2nd week.